Factors Associated with Development of Acute Kidney Injury After Liver Transplantation - Rodrigo Catalán; José V. Jiménez-Ceja; Rodolfo Rincón-Pedrero; Antonio Olivas-Martínez; Armando J. Martínez-Rueda; Silvana Bazúa-Valenti; Diego L. Carrillo-Pérez; Leoneli I. Grajeda-Medina; Ignacio García-Juarez; Mario Vilatobá; Juan A. Ortega-Trejo; Rosalba Pérez-Villalva; et al. (Permanyer, 2022)
Background: Early post-liver transplant (LT) acute kidney injury (AKI) has been associated with worse short-term and long-term outcomes, but the incidence and risk factors in our population are unknown. Methods: We designed a prospective, singlecenter, longitudinal cohort study to determine the incidence of AKI during the immediate postoperative period of LT, and to identify the risk factors associated with AKI after LT. Pre-operative and intraoperative variables were analyzed to determine if there was any correlation with the development of post-operative AKI. Results: Eighty-six patients were included in the final analysis; from them, 45 (52%) developed AKI in the following 30 days after LT. The presence of hepatic encephalopathy prior to LT was the factor most strongly associated with the development of AKI (Relative Risk 3.67, 95% Confidence Interval 1.08-8.95). Other factors associated with AKI development were male gender and a higher serum lactate during surgery. Conclusion: AKI was a frequent complication that significantly worsened the prognosis of LT recipients and was associated with an increased 30-day mortality rate. The presence of hepatic encephalopathy strongly predicted the development of severe AKI.